NZ J Ecol 2017
DOI: 10.20417/nzjecol.41.14
|View full text |Cite
|
Sign up to set email alerts
|

Native woody plant recruitment in lowland forests invaded by non-native ground cover weeds and mammals

Abstract: Globally, lowland forests have been depleted, fragmented, and degraded by land clearance and conversion by humans. Many remnants are also invaded by non-native plants and mammals, which can exacerbate biodiversity loss and impede ecosystem recovery. We examined the effects of non-native ground cover weeds and mammals on the seedling recruitment of native woody plants in lowland forests in northern New Zealand by following establishment over 2 years at sites experiencing different levels of weed cover, with or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Several other studies have also provided evidence for negative impact thresholds for a variety of invasive plants, including the shrub Baccharis halimifolia in Mediterranean saltmarshes (Fried and Panetta 2016), the monocarpic perennial Heracleum mantegazzianum in northern European grasslands (Thiele et al 2010b), the vine Delairea odorata in northern Californian coastal scrub and riparian communities (Alvarez and Cushman 2002), and the scrambling herbs Tradescantia fluminensis, Plectranthus ciliatus and Asparagus scandens in New Zealand temperate forests (McAlpine et al 2015). Fried and Panetta (2016) found that native species' responses to invasion were complex and, in general, non-linear across a gradient of B. halimifolia cover.…”
Section: Ecological Framework For Invasive Species Impact Thresholdsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several other studies have also provided evidence for negative impact thresholds for a variety of invasive plants, including the shrub Baccharis halimifolia in Mediterranean saltmarshes (Fried and Panetta 2016), the monocarpic perennial Heracleum mantegazzianum in northern European grasslands (Thiele et al 2010b), the vine Delairea odorata in northern Californian coastal scrub and riparian communities (Alvarez and Cushman 2002), and the scrambling herbs Tradescantia fluminensis, Plectranthus ciliatus and Asparagus scandens in New Zealand temperate forests (McAlpine et al 2015). Fried and Panetta (2016) found that native species' responses to invasion were complex and, in general, non-linear across a gradient of B. halimifolia cover.…”
Section: Ecological Framework For Invasive Species Impact Thresholdsmentioning
confidence: 99%
“…following a threshold relationship. McAlpine et al (2015) reported that patterns of native plant species decline varied amongst the three weed species in the temperate forest, with only T. fluminensis and P. ciliatus exerting negative threshold effects on native species richness at approximately 50 % weed volume. It is clear from these studies that rates of species decline and the position of the threshold zone varies from one invasive species to another, and may depend upon the functional identity of the native vegetation within the recipient community.…”
Section: Ecological Framework For Invasive Species Impact Thresholdsmentioning
confidence: 99%
See 2 more Smart Citations
“…Widespread ground cover weed species such tradescantia (Tradescantia fluminensis) and climbing asparagus (Asparagus scandens) have well-documented negative impacts on native plant communities in New Zealand (Kelly & Skipworth 1984a;Standish et al 2001;McAlpine et al 2017), and are thus frequently targeted in weed control programmes. At sites with few native species in the understory, non-target damage may not be a problem.…”
Section: Introductionmentioning
confidence: 99%